The ATM-Chk2-Cdc25A checkpoint pathway guards against radioresistant DNA synthesis - Falck, J; Mailand, N; Syljuasen, R.G; Bártek, Jiří; Lukáš, Jiří (Nature, 2001)
When exposed to ionizing radiation (IR), eukaryotic cells activate checkpoint pathways to delay the progression of the cell cycle. Defects in the IR-induced S-phase checkpoint cause 'radioresistant DNA synthesis', a phenomenon that has been identified in cancer-prone patients suffering from ataxia-telangiectasia, a disease caused by mutations in the ATM gene. The Cdc25A phosphatase activates the cyclin-dependent kinase 2 (Cdk2) needed for DNA synthesis, but becomes degraded in response to DNA damage or stalled replication. Here we report a functional link between ATM, the checkpoint signalling kinase Chk2/Cds1 (Chk2) and Cdc25A, and implicate this mechanism in controlling the S-phase checkpoint. We show that IR-induced destruction of Cdc25A requires both ATM and the Chk2-mediated phosphorylation of Cdc25A on serine 123. An IR-induced loss of Cdc25A protein prevents dephosphorylation of Cdk2 and leads to a transient blockade of DNA replication. We also show that tumour-associated Chk2 alleles cannot bind or phosphorylate Cdc25A, and that cells expressing these Chk2 alleles, elevated Cdc25A or a Cdk2 mutant unable to undergo inhibitory phosphorylation (Cdk2AF) fail to inhibit DNA synthesis when irradiated. These results support Chk2 as a candidate tumour suppressor, and identify the ATM-Chk2-Cdc25A-Cdk2 pathway as a genomic integrity checkpoint that prevents radioresistant DNA synthesis.
Keywords: DNA vazebné proteiny; Animals; buněčné linie; Radiation Tolerance; Radiation, Ionizing; nádorové supresorové proteiny; Cell Cycle; transfekce; Transfection; serin; lidé; fosfatasy cdc25; Checkpoint Kinase 2; S Phase; tolerance záření; proteinkinasy; replikace DNA; Mice; Protein Serine-Threonine Kinases; signální transdukce; ATM protein; myši; Signal Transduction; ionizující záření; checkpoint kinasa 2; Cell Line; buněčný cyklus; Cell Cycle Proteins; Tumor Suppressor Proteins; fosforylace; DNA-Binding Proteins; alely; cdc25 Phosphatases; Serine; Alleles; Ataxia Telangiectasia Mutated Proteins; Protein Kinases; S fáze; zvířata; DNA Replication; proteiny buněčného cyklu; protein-serin-threoninkinasy; Phosphorylation; Humans